The Effects of Fatiguing Aerobic Exercise on the Cerebral Blood Flow and Oxygen Extraction in the Brain: A Piloting Neuroimaging Study - Bao, Dapeng; Zhou, Junhong; Hao, Ying; Yang, Xuedong; Jiao, Wei; Hu, Yang; Wang, Xiaoying (Frontiers in Neurology, 2019)
The fatigue in aerobic exercise affects the task performance. In addition to the fatigue in the muscular system, the diminished performance may arise from the altered cerebral blood supply and oxygen extraction. However, the effects of the fatiguing aerobic exercise on the ability of brain to regulate the cerebral blood flow (CBF) and to extract the oxygen are not fully understood. In this pilot study, we aim to quantify such effects via advanced functional MRI techniques. Twenty healthy younger elite athletes were recruited. In the screening visit, one circle ergometer test was used to screen the maximal relative oxygen consumption (VO2max). Eleven eligible participants then completed the next MRI visit after 7 days. These participants completed a 2-minute pulsed arterial spin labeling (ASL) using the PICORE/QUIPSS II and 5-minute asymmetric spin echo (ASE) scan at baseline and immediately after the aerobic circle ergometer test. The CBF was then measured using the ASL images and the oxygen consumption of the brain was quantified using oxygen extraction fractions (OEF) derived from the ASE images. The test time, VO2max, and anaerobic threshold were also recorded. As compared to baseline, participants had significant reduction of global CBF (p=0.003). Specifically, the CBF in bilateral striatum, left middle temporal gyrus (MTG) and right inferior frontal gyrus (IFG) decreased significantly (p<0.005, K>20). No significant changes of the OEFs were observed. Participants with greater OEF within the right striatum at baseline had longer test time, greater anaerobic threshold and relative VO2max (r2>0.51, p<0.007). Those with longer test time had less reduction of CBF within the right IFG (r2=0.55, p=0.006) and of OEF within the left striatum (r2=0.52, p=0.008). Additionally, greater anaerobic threshold was associated with less reduction of OEF within the left MTG (r2=0.49, p=0.009). This pilot study provided first-of-its-kind evidence suggesting that the fatiguing aerobic exercise alters the cerebral blood supply in the brain, but has no significant effects on the ability of brain to extract oxygenation. Future studies are warranted to further establish the CBF and OEF as novel markers for physical and physiological function to help the assessment in the sports science and clinics.